Potential Source Areas for Atmospheric Lead Reaching Ny-Ålesund from 2010 to 2018 - Andrea Bazzano; Stefano Bertinetti; Francisco Ardini; David Cappelletti; Marco Grotti (Atmosphere, 2021)
Lead content, enrichment factors, and isotopic composition (208Pb/206Pb and 207Pb/206Pb) measured in atmospheric particulate matter (PM10) samples collected for nine years at Ny-Ålesund (Svalbard islands, Norwegian Arctic) during spring and summer are presented and discussed. The possible source areas (PSA) for particulate inferred from Pb isotope ratio values were compared to cluster analysis of back-trajectories. Results show that anthropogenic Pb dominates over natural crustal Pb, with a recurring higher influence in spring, compared to summer. Crustal Pb accounted for 5–16% of the measured Pb concentration. Anthropogenic Pb was affected by (i) a Central Asian PSA with Pb isotope signature compatible with ores smelted in the Rudny Altai region, at the Russian and Kazakhstan border, which accounted for 85% of the anthropogenic Pb concentration, and (ii) a weaker North American PSA, contributing for the remaining 15%. Central Asian PSA exerted an influence on 71–86% of spring samples, without any significant interannual variation. On the contrary, 59–87% of summer samples were influenced by the North American PSA, with higher contributions during 2015 and 2018. Back-trajectory analysis agreed on the seasonal difference in PSA and highlighted a possible increased influence for North American air masses during summer 2010 and 2018, but not for summer 2015.